DETERMINANTS OF PAYLATER USAGE AMONG GENERATION Z IN DENPASAR CITY - Ni Kadek Indah Kristina Dewi; Surya Dewi Rustariyuni (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2026)
The development of Buy Now Pay Later (PayLater) services in Indonesia has experienced rapid growth alongside the expansion of digital transactions and the high adoption of financial technology among Generation Z. Denpasar City, as the center of economic activities in Bali Province, exhibits relatively high levels of consumption and digital literacy, which may encourage the utilization of PayLater services. However, the factors influencing the intention to use PayLater have produced inconsistent findings across previous studies. This study aims to analyze the effects of performance expectancy, social influence, and trust on the intention to use PayLater among Generation Z in Denpasar City. The research was conducted in Denpasar City with a sample of 100 respondents selected using a purposive sampling technique. Data were collected through questionnaire distribution and analyzed using multiple linear regression analysis. The results indicate that performance expectancy, social influence, and trust simultaneously have a significant effect on the intention to use PayLater among Generation Z in Denpasar City. Partially, performance expectancy and trust have a positive and significant effect on the intention to use PayLater, while social influence has a positive but insignificant effect. These findings suggest that perceived benefits and trust in PayLater services are more dominant factors in shaping usage intention than social influence. The implications of this study indicate that PayLater service providers should enhance service benefits, system security, information transparency, and service credibility to increase the intention to use PayLater among Generation Z. Furthermore, the findings support the application of the UTAUT2 model in explaining the intention to adopt digital financial technology.